Acid attack followed by calcination treatment as a strategy for the development of porous geopolymers applied to the adsorption of azo dyes - Tochetto, Gabriel André (2023)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2023.